Imaging the facet surface strain state of supported multi-faceted Pt nanoparticles during reaction - Dupraz, Maxime; Li, Ni; Carnis, Jérôme; Wu, Longfei; Labat, Stéphane; Chatelier, Corentin; van de Poll, Rim; Hofmann, Jan P.; Almog, Ehud; Leake, Steven J.; Watier, Yves; Lazarev, Sergey; et al. (Nature communications, 2022)
Nanostructures with specific crystallographic planes display distinctive physico-chemical properties because of their unique atomic arrangements, resulting in widespread applications in catalysis, energy conversion or sensing. Understanding strain dynamics and their relationship with crystallographic facets have been largely unexplored. Here, we reveal in situ, in three-dimensions and at the nanoscale, the volume, surface and interface strain evolution of single supported platinum nanocrystals during reaction using coherent x-ray diffractive imaging. Interestingly, identical { hkl } facets show equivalent catalytic response during non-stoichiometric cycles. Periodic strain variations are rationalised in terms of O 2 adsorption or desorption during O 2 exposure or CO oxidation under reducing conditions, respectively. During stoichiometric CO oxidation, the strain evolution is, however, no longer facet dependent. Large strain variations are observed in localised areas, in particular in the vicinity of the substrate/particle interface, suggesting a significant influence of the substrate on the reactivity. These findings will improve the understanding of dynamic properties in catalysis and related fields. Understanding strain dynamics and their relationship with crystallographic facets have been largely unexplored. Here the authors demonstrate how the 3D lattice displacement and strain evolution depend on the crystallographic facets of Pt nanoparticles during CO oxidation reaction, providing new insights in the relationship between facet-related surface strain and chemistry.